"Motherhood brings Joy and Happiness", Discourses of the Ideal Mother in South Africa - Levey, Laura (Department of Psychology, 2024)
This research explores the effect of mothering ideologies found in dominant discourses by examining the discourses mothers draw on when describing mothering. First-time mothers who attended perinatal care in public healthcare centres are often faced with interventions like the First 1000 Days of Life Campaign drawn from the Global North. Using Thematic Discourse Analysis, the dominant effect discourses have on South African women's experiences, and practices of mothering will be explored. This research draws on 12 interviews with first-time mothers in low-income areas in Cape Town, exploring first-time mothers' experiences of motherhood. There is limited research on how patriarchal values imposed by the Global North affect South African mothers' discourses and experiences of motherhood. The research took the form of secondary data analysis of semi-structured interviews. Thematic Discourse Analysis was used to discern dominant discourses in the qualitative data. An intersectional feminist lens was used to highlight significant discourses identified through the literature. Results: The analysis highlighted three primary discourse themes. Discourses of the ideal mother had three subthemes: motherhood comes naturally and brings fulfilling joy, mothers should be baby-centred, and good mothers are professionally guided. These medicalised mothering ideals from the Global North promulgated by the medical fraternity left many mothers feeling unsure of their own mothering knowledge and choices. Discourses of the ideal mother often split mothers into good or bad mothers. Discourses of the present mother and absent father were identified and often resulted in discourses of mothering in poverty. Discourses that contested patriarchal gender norms were found to be omitted. Mothers revealed high levels of stress, shame and impoverishment. Asymmetrical power dynamics favouring men combined with a systemic lack of supportive social and economic policies for mothers often resulted in their oppression, grant dependence and poverty. Conclusion: The research demonstrated the ways in which local mothers' mothering practices were significantly entrenched in powerful patriarchal ideologies promulgated by medical and social discourses. Ideologies imposed on mothers through primary healthcare facilities were shown to cause mothers uncertainty, anxiety and fears of inadequacy. Lack of adequate social support through the child grant was shown to maintain systems of class and gender inequity and often resulted in significant impoverishment. Key words: motherhood, mothering ideals, discourse analysis, primary healthcare, perinatal healthcare